2014
DOI: 10.1186/1471-2253-14-70
|View full text |Cite
|
Sign up to set email alerts
|

Multiple epidural steroid injections and body mass index linked with occurrence of epidural lipomatosis: a case series

Abstract: BackgroundEpidural lipomatosis (EL) is an increase of adipose tissue, normally occurring in the epidural space, sufficient to distort the thecal sac and compress neural elements. There is a lack of knowledge of risk factors, impact on patient’s symptoms, and its possible association with epidural steroid injections.MethodsHistory, physical examination, patient chart, and MRI were analyzed from 856 outpatients referred for epidural steroid injections. Seventy patients with signs of EL on MRI comprised the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 39 publications
1
42
0
1
Order By: Relevance
“…Epidural steroid injection has also been postulated as a cause of SEL. [43][44][45][46] However, others have reported it as a treatment. 47 The current authors found no difference in history of epidural steroid injections between the SEL group and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Epidural steroid injection has also been postulated as a cause of SEL. [43][44][45][46] However, others have reported it as a treatment. 47 The current authors found no difference in history of epidural steroid injections between the SEL group and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive systemic exogenous steroid use accounts for 55% of cases 2. Other causes include obesity and Cushing’s syndrome, due to excessive endogenous steroid production 2 3. Epidural steroid injection causing SEL has also been reported 3 4.…”
Section: Introductionmentioning
confidence: 99%
“…Other causes include obesity and Cushing’s syndrome, due to excessive endogenous steroid production 2 3. Epidural steroid injection causing SEL has also been reported 3 4. Typically, SEL occurs in the lumbar region and results in thecal sac compression.…”
Section: Introductionmentioning
confidence: 99%
“…The statistical results show that the heterogeneity between the initial studies is signi cant, the source of heterogeneity may be that there is no uniform standard for the diagnosis of SEL in various studies. Four studies [17][18][19][20] de ned SEL as an EF/SpiC index greater than 0.4 or 0.6, four reviews [21][22][23][24] diagnosed as SEL based on MRI showing enlarged fat tissue compressing the dura sac, two studies [14,25] obtained the diagnosis basis based on clinical symptoms and signs and MRI imaging but did not clearly explain. After excluding articles by the one-by-one elimination method, the heterogeneity between studies was signi cantly reduced (I 2 = 17%).…”
Section: Risk Of Biasmentioning
confidence: 99%